The Influence of Team Building & Participation on Team Trust, Team Cohesion and Project Performance Among Project Managers in Malaysia - Fung, Han Ping; Cheng, Sheila (AeU, 2015)
Forming project teams to implement various services are prevalent in many organizations today as organizations believe a project team’s performance exceeds the total sum of individual outputs. According to Project Management Institute (PMI), one of the critical interpersonal skills expecting from a project manager is team building as this skill can motivate the team to achieve the project goals. However, there is limited study to evaluate how team building & participation can influence team trust, team cohesion and project performance among project managers in Malaysia. This study has developed a research model extended from the research work conducted by Cohen and Bailey (1997). Based on the data collected and analysis conducted, this study provides empirical evidence that project managers need to initiate more team building & participation sessions as these can increase the team trust and improve the project performance. Moreover, project managers also need to promote team trust as this can improve team cohesion. However, project managers also need to be mindful about the negative consequence when their project teams are too cohesive. At the same time project managers need to manoeuvre wisely the project team size and project duration so that these two factors are not negatively impacting the team cohesion and the project performance. The outcome of this study has shed some lights in explaining the relationships among attitudinal, behavioral and performance outcomes derived from Cohen and Bailey (1997). Moreover, this study also provided some guidance to project managers how to improve team trust and project performance through team building & participation. Discussion, conclusion, limitation and future research are also incorporated in this paper.